La perspectiva docente acerca de la noción de familia de niños y niñas preescolares costarricenses y extranjeros centroamericanos - Arce Villalobos, Doris Rocío (2005)
Article based on the results and conclusions drawn in a research about the concept of family held by Costa Rican and foreign Central American preschoolers. The concept these children have is closely related to the real-life experiences they have lived. It was possible to establish a difference since —according to the teachers— Costa Ricans view the family as nuclear while foreign children view it as extensive since they consider that relatives living outside the household are also part of the family.